The impact of major congenital anomalies on obstetric outcomes in the United Arab Emirates: the Mutaba’ah Study - Hiba Adam; Nadirah Ghenimi; Anne F Minsart; Hassib Narchi; Shamsa Al Awar; Omniyat M Al Hajeri; Iffat Elbarazi; Rami H. Al-Rifai; Luai A. Ahmed (Scientific Reports)
Abstract Major congenital anomalies (MCAs) are a public health concern. However, studies on obstetric outcomes in pregnancies complicated by MCAs are scarce, emphasizing the need for research to enhance management strategies. This study aimed to investigate the impact of MCAs on fetal presentation and delivery mode in the United Arab Emirates. The analysis was based on a cohort of single live births in the Mutaba’ah study (2017–2023). Univariable and multivariable regression models assessed the associations between MCAs and obstetric outcomes, adjusting for maternal and neonatal characteristics. For any and single MCAs, significant associations with breech presentation were detected in women below 35 years (AOR = 2.7, 95% CI: 1.5-5.0; AOR = 2.5, 95% CI: 1.3–4.8) and among term deliveries (AOR = 2.5, 95% CI: 1.4–4.3; AOR = 2.4, 95% CI: 1.3–4.3). These associations remained significant in young (< 35 years) multiparous and older (≥ 35 years) nulliparous, as well as among term multiparous and preterm nulliparous women. The association with cesarean delivery was significant among multiparous below 35 years, where mothers of neonates with any MCAs had twice the odds of cesarean delivery (AOR = 2.1, 95% CI: 1.3–3.4). This study revealed a significant association between MCAs and the risk of breech presentation and cesarean delivery, varying by maternal age, gestational age, and parity. These findings underscore the need for early detection of MCAs in pregnancy, as this may help avoid obstetric complications. However, addressing the risk factors for MCAs and promoting a multidisciplinary approach would lead to even better outcomes for both mother and newborn.